Artificial Intelligence and Journalism: an Approach to the Portuguese Context - Mgt. Adriana GONÇALVES,Dr. Paulo Victor MELO (Fonseca, Journal of Communication, 2023)
In recent years, various newspapers around the world have used algorithms and artificial intelligence in news produc-tion. In Portugal, the examples of news production using these technologies are rare, as are the studies on the subject. The incipient work that relates artificial intelligence and algorithms to journalism in Portugal is detectable in the Con-gresses of Sopcom